1982
DOI: 10.1095/biolreprod27.3.575
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Migration of the Porcine Embryo: Influence of Estradiol-17β and Histamine

Abstract: The role of estradiol-17 beta (E2) in migration of the porcine embryo was examined (Experiment 1) by observing the distribution of Silastic (polydimethyl siloxane, Medical Adhesive Silicone Type A, Dow Corning) beads impregnated with cholesterol or E2 (n=5 gilts per treatment) after 5 days in utero (Day 12 of the estrous cycle, Day 0=1st day of estrus). Beads impregnated with E2 migrated farther (P less than 0.05) than those impregnated with cholesterol. Twenty additional gilts and sows were used to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
3

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 14 publications
1
34
0
3
Order By: Relevance
“…However, analysis of 12 scNT-derived placentas revealed that all fetuses had severe placental abnormality. An early pregnancy loss or first-trimester miscarriage in the control is the most common complication in pig reproduction, with an incidence range between 20 and 30% of all conceptions, and another 10-15% loss occurs at midgestation (Pope et al, 1982;Stroband et al, 1990;Pope, 1994). Embryonic loss can be derived from the embryo and/or the uterine environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, analysis of 12 scNT-derived placentas revealed that all fetuses had severe placental abnormality. An early pregnancy loss or first-trimester miscarriage in the control is the most common complication in pig reproduction, with an incidence range between 20 and 30% of all conceptions, and another 10-15% loss occurs at midgestation (Pope et al, 1982;Stroband et al, 1990;Pope, 1994). Embryonic loss can be derived from the embryo and/or the uterine environment.…”
Section: Discussionmentioning
confidence: 99%
“…Early embryonic mortality occurs in high frequency during a period of gestation known as the embryonic period: 20-30% of pig fetuses die between gestational day 12 and 30, and another 10-15% loss occurs at midgestation (Geisert et al, 1982;Pope et al, 1982;Pope and First, 1985;Stroband and Van der Lende, 1990;Pope, 1994;Geisert and Schmitt, 2001). The factors implicated as the causes of early embryonic mortality can be broadly categorized as intrinsic (endometritis and periglandular fibrosis) (Parker et al, 2004;Inagaki et al, 2005), extrinsic (environmental or management-related factors, such as stress, poor nutrition, and body condition) (Lucy, 2001;Eugster et al, 2004;Campagne, 2006), or embryonic factors (Geisert et al, 1982;Pope and First, 1985;Geisert and Yelich, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Although the full significance of this synthesis has not yet been established, it is presumed that estrogens play a role in the maintenance of pregnancy. A similar situation occurs in early pregnancy in the pig, where estrogen synthesis by the blastocyst is seen around days 10-12 of pregnancy (Perry et al 1973), a time when 17b-estradiol (E 2 ) has been shown to influence intrauterine migration of embryos (Pope et al 1982) and uterine prostaglandin F 2a secretion (Bazer & Thatcher 1977). Estrogen formation by the early pig embryo is limited in duration with a transient expression of cytochrome P450 aromatase (P450 arom ) enzyme in the trophoblast, between days 10 and 12 (Conley et al 1992(Conley et al , 1994.…”
Section: Introductionmentioning
confidence: 81%
“…Blastocyst-derived oestrogens could participate in early porcine pregnancy by initiating blastocyst spacing (Pope et al 1982), stimulating endometrial secretion (Geisert et al 1982b), promoting luteal maintenance (Gardner et al 1963;Ford and Magness 1980) or by stimulating uterine blood-flow (Dickson et al 1969;Ford et al 1982). By regulating calcium flux in endometrial cells, oestrogens of conceptus origin (Fishel 1979) could also activate phospholipase and thereby enhance local PG synthesis (Rubin and Laychock 1978).…”
Section: Discussionmentioning
confidence: 99%